Analisis Sertifikasi Tenaga Ahli Dan Terampil Di Kalimantan Tengah Tahun 2019 - Maretina Eka Sinta (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Workers who have been declared competent will receive a certificate as proof of competence. The certificate serves as proof of competence, the certificate holder will treat the certificate as part of the pride, proof of ability as well as recognition of the knowledge it has. Based on the results of the study using the Frequency Distribution method, the results show that the presence of Experts and Skilled civil certified in Palangka Raya City has a significant effect on the progress of the construction world in Palangka Raya City with the relative frequency (F) value of 57.50% ≥ 50, 00% 75.00% and the high level of ability of Experts and Skills to overcome technical problems in the field with a relative frequency (F) value of 60.00% ≥ 50.00% 75.00%, which means it is satisfactory. Taking into account the results of research on the existence of experts and skilled workers who have had a real positive influence on the progress of the world of construction especially in the City of Palangka Raya, it is deemed necessary that every construction work is required to involve competent and certified experts and skilled civilians so that the quality of work construction can be maintained. Furthermore, in order to maintain continuity and anticipate the progress of the construction world, it is deemed necessary that certified experts and skilled civilians always learn and update their knowledge by always learning, either through training activities, seminars or workshops